Analysis of the Risk of Work Accidents in High-Story Building Construction Projects using the FMEA (Failure Modes and Effects Analysis) Method - Meylinda Sabrinawati; I Nyoman Dita Pahang Putra (PT FORMOSA CENDEKIA GLOBAL, 2024)
A construction project is a complex and exciting process, starting from planning and design, through to implementation and finishing. The process of building a construction project always has risks at every stage of its implementation. To prevent and minimize risks that could cause work accidents and losses on the project, it is necessary to carry out a work accident risk analysis on the project. This research carried out a work accident risk analysis on the Joint Lecture Building and FISIP Laboratory Phase 2 UPN